1996
DOI: 10.1006/viro.1996.0210
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Placement of a Coronavirus Promoter Results in Enhanced mRNA Synthesis from the Downstream-Most Initiation Site

Abstract: Insertion of the 17-nucleotide promoter region for the bovine coronavirus N gene as part of a 27-nucleotide cassette into the open reading frame of a cloned synthetic defective-interfering (DI) RNA resulted in synthesis of subDI RNA transcripts from the replicating DI RNA genome. Duplicating and triplicating the promoter sequence in tandem caused a progressive increase in the efficiency of subgenomic mRNA synthesis despite a concurrent decrease in the rate of DI RNA accumulation that was not specific to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 6 publications
(6 reference statements)
10
36
0
Order By: Relevance
“…These studies support a mechanism of discontinuous negative-strand synthesis reminiscent of the process of copy choice RNA recombination (39). Clearly, transcription attenuation is an attractive hypothesis which deserves serious attention, as it is consistent with the available data presented in this and other reports and represents a more direct mechanism to regulate subgenomic RNA synthesis (9,14,18,25,38). Recent UV transcription-mapping studies with mRNA transcribed from DI RNAs, however, have suggested that the subgenomic mRNAs directly originate from genome-length templates (16,24).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These studies support a mechanism of discontinuous negative-strand synthesis reminiscent of the process of copy choice RNA recombination (39). Clearly, transcription attenuation is an attractive hypothesis which deserves serious attention, as it is consistent with the available data presented in this and other reports and represents a more direct mechanism to regulate subgenomic RNA synthesis (9,14,18,25,38). Recent UV transcription-mapping studies with mRNA transcribed from DI RNAs, however, have suggested that the subgenomic mRNAs directly originate from genome-length templates (16,24).…”
Section: Discussionsupporting
confidence: 86%
“…This model predicts that all subgenomic negative strands originate from the genomic RNA directly, rather than from mRNA. In support of this hypothesis, tandem placement of a coronavirus promoter resulted in enhanced mRNA synthesis from the downstream-most initiation sites (18). During EAV transcription, the IG element in subgenomic mRNA is derived from the IG sequences encoded in the genomic RNA during negative-strand synthesis rather than from leader sequences encoded at the 5Ј end of the genome.…”
Section: Discussionmentioning
confidence: 91%
“…However, studies with DI RNAs containing authentic and mutated TRSs led many investigators to conclude that, beyond a minimum threshold of potential base pairing, other factors must predominate (Hiscox et al, 1995;Makino et al, 1991;van der Most et al, 1994). DI RNA studies thus provided the first indication of the importance of the local sequence context of the TRS and the position of the TRS relative to the 3 0 end of the genome (Joo and Makino, 1995;Krishnan et al, 1996;Ozdarendeli et al, 2001;van Marle et al, 1995).…”
Section: A Replication and Transcriptionmentioning
confidence: 99%
“…We attempted to identify putative TRSs upstream of all ORFs, both known and predicted (Tables 2 and 3). However, TRSs are not required for transcription of all coronavirus genes, because internal initiation from larger RNA transcripts is also able to facilitate translation (18,19). Certain ORFs overlap (ORFs 10 and 11, by 12 amino acids; Fig.…”
mentioning
confidence: 99%